Результати дослідження характеристик датчика тиску комп‘ютерної системи діагностики ДВЗ - Смолін, Юрій Олександрович (Національний технічний університет "Харківський політехнічний інститут", 2019)
Розглянуто основні вимоги до сучасних датчиків. Виділено параметри, які найбільш суттєво впливають на якісні характеристики датчиків. Визначено частину недоліків датчиків, що можна компенсувати за рахунок обчислювальних і логічних можливостей комп’ютера. Наведено структурну схему розробленого датчика, розгорнення зовнішньої поверхні тензометричного стакану зі схемою наклейки тензорезисторів й схемою їх розпаювання, конструкцію датчика і його опис, креслення мембрани, а також необхідні характеристики датчика тиску. Розглянуто процес одержання градуйованих характеристик. Обрані засоби контролю і вимірювання та наведені їх характеристики. Наведено розроблену структурну схему експериментальної установки для визначення градуйованих характеристик. Отримані й наведені градуйовані характеристики первинного вимірювального перетворювача, підсилювача, АЦП і цифрового датчика тиску. Проведено розрахунок чутливості датчика.

The basic requirements for modern sensors are considered. The parameters that have the most significant effect on the qualitative characteristics of the sensors are selected. The part of flaws of sensors that can be compensated by computational and logic capabilities of the computer is determined. The structural scheme of the developed sensor, the unwrapping of the outer surface of the strain gauge glass with the scheme of strain gauge stickers and their decomposition scheme, the design of the sensor and its description, the drawing of the membrane, as well as the necessary characteristics of the pressure sensor are provided. In this case, the main attention is paid to the circuit of the primary measuring transducer, the method of setting the strain gauge, the circuit of their connection and the power supply. A detailed description of all mechanical components of the sensor and its cooling method is given. The process of obtaining the graded characteristics is considered. The means of control and measurement and their characteristics are selected. The developed structural scheme of the experimental setup for the determination of the graded characteristics is given. The graduated characteristics of the primary measuring transducer, amplifier, ADC and digital pressure sensor are derived and presented. The sensitivity of the sensor is calculated.
Research results of pressure sensor characteristics computer ice diagnostic systems ІСЕ
Keywords: первинні перетворювачі; експериментальна установка; градуйовані характеристики; чутливість датчика; primary transducers; experimental setup; graded characteristics; sensitivity of the sensor